Malware phylogeny oriented to libraries analysis - Gutiérrez-Cárdenas, Juan Manuel (2016)
In the field of computational biology, phylogeny is used to recognize the existing similarity between various species as well as the evolution engine (force) that has enabled these species to show modifications as time goes by. The use of these phylogeny techniques with a focus on computer viruses has allowed the finding of similarities between different malware families. This study presents the implementation of a proof of concept through the application of a technique used in the bioinformatics field, as is the case of the Neighbor Joining algorithm designed for the analysis of a group of computer samples. The aim will be to detect the similarity between the gathered samples, considering the similarity between the libraries of the system that uses this kind of programs.